Effective elimination of Pb (II) cations from waste water and polluted water using siderite magnetic biochar - Saeid Gitipour; Mahsa Sanaei; Razyeh Lak; Abdolreza Karbassi (Scientific Reports)
Abstract Magnetic biochar composites were created by pyrolyzing siderite and sawdust in nitrogen gas (N2). adsorption was done in a variety of pH and temperature ranges on magnetic biochar. A magnet was used to extract the MB-liquid from each other following 24-hour shaking period. At Iran’s Geological Survey, Pb(II) concentration was measured using an ICP (Inductively Coupled Plasma). The adsorption-desorption process was carried out five times in order to evaluate the magnetic biochar’s reusability. The Pyrolysis of siderite in order to gain the MB changes its chemical composition and turns into a mixture of hematite, magnetite and maghemite, which imparts magnetism to the biochar and enriches its surface functional groups. The characterizations showed a higher specific surface area and porous structures in the magnetic biochar. An external magnetic field (magnet) was used to easily separate the magnetic biochar suspension because XRD investigation revealed that the primary component of the siderite magnetic biochar absorbent is magnetite, a ferrimagnetic mineral with substantial magnetic characteristics. The magnetic biochar composites’ strong adsorption capabilities toward Pb (II) ions were demonstrated by the batch adsorption tests. At pH 5.0 and T = 45 °C, Pb had its highest adsorption capability on magnetic biochar 96.92%. The mesoporous structure of magnetic biochar was indicated by the type IV isotherm. It has been demonstrated that adsorption most closely matches Langmuir’s model. Therefore, it can be said that monolayer adsorption has occurred. Biochar’s active sites were probably responsible for the fast adsorption process. Kinetics of lead adsorption with MB have been harmonized with pseudo-second order, indicating that the predominant mechanism for Pb adsorption onto magnetic biochar is chemisorption/surface complexation. In summary, magnetic biochar serves as a dual-functional material, adsorbing Pb(II) species and reducing them to less harmful forms, with the added advantage of easy recovery and reuse due to its magnetic properties. This makes it a promising material for the remediation of lead-contaminated environments.